TANGGAP BEBERAPA VARIETAS BAWANG MERAH (Allium ascalonicum L.) TERHADAP PEMBERIAN Trichoderma sp - Cicilia Sihombing; Hot Setiado; Hasmawi Hasyim (Jurnal Agroekoteknologi, 2013)
attempts to do that is the use of high yielding varieties. This study aimed to determine the effect of four doses of Trichoderma extent on the growth and production of some onion varieties, which have been implemented in Simalingkar, excl. Tuntungan Field from May  to August 2012. This study used a randomized block design factors ie double dose Trichodema first factor with 4 levels, namely 0 g (control), 1 g , 2 g , 3 g dose. The second factor is that varieties: Medan, Bali Karet, Maja. The data obtained were analyzed using analysis of variance, followed by Test Honestly Significant Difference The results of data analysis showed that the varieties differ significantly in plant height, number of leaves, number of cloves per sample, cloves per bulb diameter. Dose Trichoderma significantly different height and dry weight of plants per plot. Interaction between Trichoderma doses and varieties have significantly influenced all parameters.   Keywords: Onion, Trichoderma dose, varieties